Structural features of doped silicon single crystals - Azarenkov, N.A.; Semenenko, V.E.; Stervoyedov, N.G. (Вопросы атомной науки и техники, 2022)
The nature of the change in the Fermi level of silicon under the influence of dopants, point defects, and dislocations has been determined. The parameters of the diffusion of impurities, the conditions for their appearance and removal in the process of directional crystallization and the post-crystallization period have been established. The expediency of doping silicon with boron and phosphorus was shown, and large single crystals were obtained. The mechanisms of elimination of structural defects have been clarified. The mobility and lifetime of charge carriers in perfect silicon single crystals under radiation exposure have been determined. The expediency of using p-type silicon as a base material for solar modules for space purposes is shown.